Analysis of the Liquidity Effect on Stock Return: Empirical Evidence from the UK Stock Market over the Period 1993-2008 - Jiang, Shuai-yu (2009)
This study examines the behaviour of liquidity in the UK market during the period January 1993 through December 2008. Turnover rate and relative bid-ask spread are used to proxy liquidity characteristics of stocks. The empirical results indicate that the liquidity effect does not significant in the UK market over the whole sample period and stock returns are reliably related to liquidity only during the month of January. The results hold in both cross-sectional and time series analyses, and are fairly robust even after controlling for market capitalization and book-to-market ratio in cross-sectional analysis and examining alternative holding periods for portfolios in time-series analysis. The results from the sample excluding January are quite consistent with that from the whole sample. Moreover my finding verifies that the potential liquidity premium of the least liquid portfolios and the differences in the return between the least liquid quintile and the most liquid quintile in January cannot be explained by the standard Capital Asset Pricing Model.